Coumarin Photocaging Groups Modified with an Electron‐Rich Styryl Moiety at the 3‐Position: Long‐Wavelength Excitation, Rapid Photolysis, and Photobleaching. Issue 14 (1st March 2018) - Lin, Qiuning; Yang, Lipeng; Wang, Zhiqiang; Hua, Yujie; Zhang, Dasheng; Bao, Bingkun; Bao, Chunyan; Gong, Xueqing; Zhu, Linyong
Abstract: A new class of coumarin photocaging groups modified with an electron‐rich styryl moiety at the 3‐position was constructed. The large π‐conjugated structure and stabilization of the carbocation intermediates by electron donors endowed the new photocaging groups with excellent long‐wavelength absorption, large two‐photon absorption cross‐sections, and high uncaging quantum yields. Moreover, the new photocaging groups displayed unique photobleaching properties after photocleavage as a result of the intramolecular cyclization rearrangement of a carbocation intermediate to form five‐membered ring byproducts and block the styryl conjugation at the 3‐position. These superior properties of the new photocaging groups are extremely beneficial for high‐concentration samples and thick specimens, thus extending the application of photocaging groups in many fields. Abstract : Rattling the cage : A new class of coumarin‐based photocaging groups, with an electron‐rich styryl moiety at the 3‐position, were synthesized. They feature large π‐conjugation, carbocation stabilization, and undergo an intramolecular cyclization rearrangement. Their long‐wavelength excitation, rapid photolysis, and photobleaching are beneficial for use in high‐concentration and thick specimens. D=electron donor, LG=leaving group.